Modified hood technique for single-port robot-assisted radical prostatectomy contributes to early recovery of continence - Zhang, Haoxun; Ning, Zikuan; Jia, Guang; Zhang, Guoling; Wang, Jiuliang; Liu, Hua; Tao, Boju; Wang, Chunyang (Frontiers in Surgery, 2023)
Abstract BACKGROUND AND PURPOSE: Urinary incontinence is one of the common side effects of robot-assisted radical prostatectomy (RARP). Here, we described the modified Hood technique for single-port RARP (sp-RARP) and assessed the interest of this new technique for early continence recovery. METHODS: We retrospectively reviewed 24 patients who underwent sp-RARP modified hood technique from June 2021 to December 2021. The pre-and intraoperative variables, postoperative functional and oncological outcomes of patients were collected and analyzed. The continence rates were estimated at 0 day, 1 week, 4 weeks, 3 months and 12 months after catheter removal. Continence was defined as wearing no pad over a 24 h period. RESULTS: Mean time of operation and estimated blood loss were 183min and 170mL, respectively. The postoperative continence rates at 0 day, 1 week, 4 weeks, 3 months and 12 months after catheter removal were 41.7%, 54.2%, 75.0%, 91.7% and 95.8%, respectively. There were two patients who detected positive surgical margins and no patients observed complications requiring further treatment. CONCLUSION: The modified hood technique is a safe and feasible method that provides better outcomes in terms of early return of continence, without increasing estimated blood loss and compromising oncologic outcomes.